Tötungsdelikte in der Schweiz von 1990 bis 2014 - Walser, Simone (sui generis Verlag, 2022)
Homicides are among the most serious offenses with serious consequences both for the relatives of victims and perpetrators and for the sense of security of the general population. This book is based on the Swiss Homicide Monitor, a database that includes all intentional homicides in Switzerland since 1990. The book provides clear information on the perpetrators, victims, circumstances of the crime, the motives behind the killing, the course of the procedure and the legal qualifications. Furthermore, individual specific types of homicides (homicide-suicides, mass and serial murders, etc.) are analyzed in depth.